Prevalence estimates for lower urinary tract symptom severity among men in Uganda and sub-Saharan Africa based on regional prevalence data - Bajunirwe, Francis; Stothers, Lynn; Berkowitz, Jonathan; Macnab, Andrew J. (Canadian Urological Association Journal, 2018)
Introduction: In the absence of specific regional data, the prevalence of urinary symptoms in the developing world is currently estimated. Regional prevalence data and estimates based on them have relevance for accurate planning/provision of future healthcare. We sought to extrapolate prevalence estimates for lower urinary tract symptom (LUTS) severity and associated sexual dysfunction for Uganda as a whole and sub-Saharan Africa (SSA) using newly available regional data from a community-based cohort of men in Uganda. Methods: Global Burden of Disease Study (GBDS) population statistics were applied to a regional dataset to provide prevalence estimates for Uganda and SSA; 415 men >55 years from five rural Ugandan communities had completed the International Prostate Symptom Scale (IPSS) and Epstein inventory to grade their LUTS severity and satisfaction with sexual function. Results: Prevalence rates for moderate and severe LUTS were 40.5% and 20%, respectively, in men >55 in the Ugandan regional data; associated scores for all four Epstein sexual satisfaction measures were low. GBDS population figures (2016) for men >55 years are 942 115 (Uganda) and 33.9 million (SSA); hence, scaling up from regional prevalence data suggests 381 557 and 188 423 men >55 years in Uganda, and 13 729 500 and 6 780 000 in SSA have moderate and severe LUTS, respectively, and the majority will have compromise of elements of their sexual function. Conclusions: Extrapolation from a small regional dataset (for which we have no guarantee of national or SSA representability) provides the first prevalence estimates for LUTS severity based on African data, and suggests a large proportion of men >55 years are troubled with LUTS and associated sexual dysfunction.
Keywords: lower urinary tract symptom (LUTS); Uganda; Sub-Saharan Africa